Experimental investigation on the effect of wastewater matrix on oxytetracycline mineralization using UV/H2O2 system - Rahmah, A.U. (Center for Environmental and Energy Research and Studies, 2017)
Abstract: Experiments on the mineralization of oxytetracycline in aqueous solutions using UV/H2O2 system were carried out. The mineralization process was monitored and measured as a function of total organic carbon (TOC) removal. Effect of five different water matrices on the mineralization efficiency, kinetics and the electrical energy per order was analyzed and reported. The present results showed that the percentage TOC removal, the rate constants and the electrical energy per order depend on the concentration of organics, inorganics and other impurities present in the water matrices. The value of electrical energy per order (EE/O) for the OTC mineralization is higher for more complex water matrices. Graphical Abstract: Figure not available: see fulltext. © 2017, Islamic Azad University (IAU).